The role of trefoil factor-3 in assessing the influence of different types of therapy on kidney condition in patients with ankylosing spondylitis - L. V. Plenkina; O. V. Simonova; S. V. Popova (Лечащий Врач, 2022)
The aim was to evaluate the effect of different types of therapy on kidney tubulointerstitial tissue in patients with ankylosing spondylitis by measuring the urinary excretion level of trefoil factor 3 (TFF-3). Urine samples of 50 patients (male/female = 37/13) aged 18 years and older with a confirmed diagnosis of ankylosing spondylitis and no comorbid pathology were investigated. The median age was 39 [34; 56] years, serum creatinine was 69 [60; 80] mmol/l, glomerular filtration rate was 105 [83; 119] ml/min/1,73 m2, albuminuria was 4,8 [2,6; 7,2] mg/g. 52% of patients received non-steroidal antiinflammatory drugs, 12% – disease-modifying anti-rheumatic drug, 36% – biologic medication. The TFF-3 level was measured using enzyme immunoassay. Obtained results were normalised to urinary creatinine concentration. The glomerular filtration rate was calculated using the CKD-EPI (Chronic Kidney Desease Epidemiology Collaboration) equation. The results were compared to a gender and age matched controls. The level of TFF-3 in patients with AS was higher than in the control group, the medians were 52.9 [15,9; 105,7] and 23.3 [1,9; 62,9] ng/mmol respectively (p = 0,02). The TFF-3 excretion during non-steroidal antiinflammatory drugs therapy reliably differed from disease-modifying anti-rheumatic drug, biologic medication and controls: the medians were 88,8 [30,5; 127,4], 8,4 [1,6; 16,1], 33,1 [20,6; 87,1], 23,3 [1,9; 62,9] ng/mmol, respectively (p = 0,01). TFF-3 levels did not correlate with glomerular filtration rate and albuminuria. The risk of tubulointerstitial damage with non-steroidal antiinflammatory drug therapy is higher compared with disease-modifying anti-rheumatic drug and biologic medication. Determining the TFF-3 urinary excretion level may improve diagnosis of renal tubulointerstitial alteration.